Examining and exploring the shifting nature of occupational stress and well-being - Harms, Peter D.; Perrewé, Pamela L.; Chang, Chu-Hsiang (Daisy) (Emerald Publishing Limited, 2021)
Volume 19 of Research in Occupational Stress and Well-Being explores and enhances our understanding of how stress and well-being at work can change over time. Much of the prior literature in occupational stress and well-being is designed to look at antecedents of stress and well-being, treating them as dependent variables. Although these models implicitly acknowledge the dynamic nature of stress and well-being, they are often assessed at a single time point and treated as a static end-state. This volume moves beyond this approach by explicitly examining stress and well-being as a dynamic phenomenon by examining changes in stress and well-being that happen developmentally, because of intentional interventions on the part of organizations, in response to job role or job status transitions, or which examine the ways in which changes in stress and well-being is conceptualized and assessed.
Keywords: Job stress.; Well-being.; Psychology -- Mental Health.; Occupational & industrial psychology.; elektronické knihy; electronic books